Deceleration of liver regeneration by knockdown of hepatic stimulator substance gene expression in mice - Han Lihong; Yan Bin (BIO Web of Conferences)
Hepatic stimulator substance (HSS), an active protein extracted from the liver of a newborn animal or from the residual liver after partial hepatectomy. HSS only stimulated the proliferation of hepatocytes or hepatogenic tumor cells, but had no stimulating effect on other tissue cells or non-hepatogenic tumor cells, indicating that its effect was tissue-specific. In addition, HSS can protect liver cells and reduce the damage of CCl4, galactosamine, thioacetamide and other drugs on liver cells. Although the hepatoprotective function of HSS has been understood to some extent, as a hepatogenic growth factor, the role of HSS in liver regeneration remains unclear and needs further study. To demonstrate if HSS plays a role in the regulation of liver regeneration and its possible mechanisms, we detect liver regeneration related index changes by knockdown of HSS after partial hepatectomy (PH). Results showed that knockdown of HSS lead to decreased liver regeneration, inhibit hepatocyte proliferation and impair mitochondrial. HSS can promote liver regeneration and protect liver cell function, and its protective mechanism may be related to the stabilization of liver cell membrane. In conclusion inhibition of HSS expression by shRNA during liver regeneration obviously delayed the process.